2014
DOI: 10.1007/s10548-014-0408-0
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation and Reduction of the EEG Artefact Caused by the Helium Cooling Pump in the MR Environment: Validation in Epilepsy Patient Data

Abstract: The EEG acquired simultaneously with fMRI is distorted by a number of artefacts related to the presence of strong magnetic fields, which must be reduced in order to allow for a useful interpretation and quantification of the EEG data. For the two most prominent artefacts, associated with magnetic field gradient switching and the heart beat, reduction methods have been developed and applied successfully. However, a number of artefacts related to the MR-environment can be found to distort the EEG data acquired e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 38 publications
(56 reference statements)
0
22
0
Order By: Relevance
“…Typically, these artifacts are caused by electrode motion as a result of MR scanner vibrations associated with the Helium compression pumps used for cooling down MR components, the patient ventilation system, and the room lights ( Mullinger et al, 2008a ; Mulert and Lemieux, 2009 ; Nierhaus et al, 2013 ; Neuner et al, 2014 ; Rothlübbers et al, 2014 ). In particular, the Helium pump artifact has been characterized in some systems by prominent peaks in the EEG spectrum around frequencies of 50 and 100 Hz ( Rothlübbers et al, 2014 ). The ventilation system and room lights are reflected in spectral peaks at other specific frequencies, with the former depending on the ventilation level ( Nierhaus et al, 2013 ).…”
Section: Eeg Data Qualitymentioning
confidence: 99%
“…Typically, these artifacts are caused by electrode motion as a result of MR scanner vibrations associated with the Helium compression pumps used for cooling down MR components, the patient ventilation system, and the room lights ( Mullinger et al, 2008a ; Mulert and Lemieux, 2009 ; Nierhaus et al, 2013 ; Neuner et al, 2014 ; Rothlübbers et al, 2014 ). In particular, the Helium pump artifact has been characterized in some systems by prominent peaks in the EEG spectrum around frequencies of 50 and 100 Hz ( Rothlübbers et al, 2014 ). The ventilation system and room lights are reflected in spectral peaks at other specific frequencies, with the former depending on the ventilation level ( Nierhaus et al, 2013 ).…”
Section: Eeg Data Qualitymentioning
confidence: 99%
“…Both are caused by MRI scanner systems and are therefore presumably specific to a scanner model. The HPA is mainly generated by vibrations from the cooling system of the MRI scanner, in particular from the helium pump (Nierhaus et al 2013 ; Rothlübbers et al 2014 ). The VA is caused by vibrations of the patient ventilation system of the MRI scanner (Nierhaus et al 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, both systems are important for a safe and comfortable usage of the MRI scanner and disabling them can be unwanted or not possible. Further, both artifacts are so far not well investigated and artifact reduction techniques are available for the HPA only (Rothlübbers et al 2014 ; Kim et al 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“… Can be used to disambiguate motion-related BOLD activation from true task activation in alpha-power EEG/fMRI analyses, by investigating CWL signals for signs of motion fMRI data can be analyzed to investigate dynamic BOLD network features of resting state EEG which can be corrected for scanner artifacts leading to data comparable to EEG only (also available). A very recent work by Rothlubbers et al demonstrated an elegant software-based solution to deal with Helium pump artifact when searching for interictal epileptic discharges [5] ; it would be valuable to compare this software-based method to the hardware-based CWL regression method to compare the ability to deal with the Helium pump artifact. …”
mentioning
confidence: 99%
“…A very recent work by Rothlubbers et al demonstrated an elegant software-based solution to deal with Helium pump artifact when searching for interictal epileptic discharges [5] ; it would be valuable to compare this software-based method to the hardware-based CWL regression method to compare the ability to deal with the Helium pump artifact.…”
mentioning
confidence: 99%